(3ebheGJ fLGMgG aj ehGLgI JMOjGJ GdbQf GdMGOj hGdYTQjfs - (3YGOd eMeO(B, (3RGjOs ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B,s, 2000)
(3GdeOjQI GdYQHjI aj GdeMjW GdHjFj Hjf GdMGVQ hGdeGVj(B: (3GdeJZjQGJ GdSjGSjI, GdbGfhfjI, GdeJZjQGJ GdGbJUGOjI, GdeJZjQGJ GdGLJeGYjI GdKbGajI, GdeJZjQGJ GdJcfhdhLjI, ebheGJ fLGM GdeOjQI GdYQHjI , JfejI egGQGJ GdbjGOjI, GSJKeGQ OhGaY GdGfLGR, JfejI bOQGJ RjGOI GdCYeGd, JfejI GdeSGQ GdhXjaj, JfejI THcGJ GdYdGbGJ GdhXjajI, GSJZdGd aQU GdYed GdLOjOI, GdJYGed eY GdUQGY GdJfXjej, GdJYGed eY VZhW GdYed(B.s
(3GdeQGLY U(B.115s
Keywords: (3EOGQI GdCYeGds; (3GdeQCI GdYGedIs